A Soft Approach to Counter Radicalism: The Role of Traditional Islamic Education - Syamsul Ma'arif; Leonard C. Sebastian; Sholihan Sholihan (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2020)
This study sheds light on the identity of Islamic education in Indonesia and Singapore to fight against radicalism. This study focuses on comparing Indonesia and Singapore in awakening multicultural consciousness, particularly on philosophical and practical religious education. The crisis of ideology faced by Muslim society in the world has an impact on the genesis of religious movements that legitimate violence and terrorism. This study is based on the sociological perspective and aimed at knowing the philosophical and practical construction of Islamic education in Indonesia and Singapore. The focus of this study is on preventive and persuasive deradicalization. Religious education institutions in both countries have multi principles and practices of education, which is implemented particularly in preventing Islamic ideology that teaches violent values and terrorism. Anticipating the development of understanding radicalism, in both countries, Islamic education has formulated policies that are accommodating with universal values and cosmopolitanism of Islamic civilization. Such efforts are implemented by pesantren and madrasah in Indonesia and Singapore to build harmony among fellow human beings and transmit the character of egalitarian, democratic, humanist, inclusive, and civilized.